Programming interactivity : a designer's guide to processing, Arduino, and openFrameworks. - Noble, Joshua, ....- (Beijing : O'Reilly, 2009)
This primer on interaction design shows artists and designers how to use 2D and 3D graphics, sound, physical interaction, computer vision, and more, to create interfaces and applications for commercial, playful, experimental, or artistic projects.